Assessment of pain during rest and during activities in the postoperative period of cardiac surgery - Larissa Coelho de Mello; Silvio Fernando Castro Rosatti; Priscilla Hortense (Universidade de São Paulo, 2014)
OBJECTIVE: to assess the intensity and site of pain after Cardiac Surgery through sternotomy during rest and while performing five activities. METHOD: descriptive study with a prospective cohort design. A total of 48 individuals participated in the study. A Multidimensional Scale for Pain Assessment was used. RESULTS: postoperative pain from cardiac surgery was moderate during rest and decreased over time. Pain was also moderate during activities performed on the 1st and 2nd postoperative days and decreased from the 3rd postoperative day, with the exception of coughing, which diminished only on the 6th postoperative day. Coughing, turning over, deep breathing and rest are presented in decreased order of intensity. The region of the sternum was the most frequently reported site of pain. CONCLUSION: the assessment of pain in the individuals who underwent cardiac surgery during rest and during activities is extremely important to adapt management and avoid postoperative complications and delayed surgical recovery.